2018
DOI: 10.1016/j.fertnstert.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type 3 intramural fibroids on in vitro fertilization–intracytoplasmic sperm injection outcomes: a retrospective cohort study

Abstract: Our results suggest that type 3 fibroids exert a negative impact on the rates of implantation, clinical pregnancy, and live birth in patients undergoing IVF-ICSI, but do not significantly increase the clinical miscarriage rate. The deleterious impact of type 3 fibroids was remarkable in women with type 3 fibroids with TD or SD >2.0 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 18 publications
(25 reference statements)
3
47
0
Order By: Relevance
“…Given the evidence that contact with the endometrium is associated with impaired decidualization, it could be hypothesized that ''intramural'' myomas that are in contact with the endometrium may have a very different impact on implantation than those with myometrium between the myoma and the endometrium. For example, a recent study that used the FIGO classification system demonstrated that single or multiple type 3 leiomyomas, R2 cm in diameter, individually or collectively, were associated with a lower implantation rate as well as a reduced rate of clinical pregnancy and delivery (129). Biochemical pregnancy (29.1% vs. 51.4%), implantation (22.7% vs. 34.4%), clinical pregnancy (27.8% vs. 43.9%), and live birth rates (21.2% vs. 34.4%) were significantly reduced in the women with type 3 myomas compared with controls.…”
Section: Leiomyomasmentioning
confidence: 99%
“…Given the evidence that contact with the endometrium is associated with impaired decidualization, it could be hypothesized that ''intramural'' myomas that are in contact with the endometrium may have a very different impact on implantation than those with myometrium between the myoma and the endometrium. For example, a recent study that used the FIGO classification system demonstrated that single or multiple type 3 leiomyomas, R2 cm in diameter, individually or collectively, were associated with a lower implantation rate as well as a reduced rate of clinical pregnancy and delivery (129). Biochemical pregnancy (29.1% vs. 51.4%), implantation (22.7% vs. 34.4%), clinical pregnancy (27.8% vs. 43.9%), and live birth rates (21.2% vs. 34.4%) were significantly reduced in the women with type 3 myomas compared with controls.…”
Section: Leiomyomasmentioning
confidence: 99%
“…Any role of nonindenting fibroids in infertility remains to be determined, with some researchers finding no impact on fertility and others indicating a negative effect. [16][17][18][19][20][21][22][23] With regard specifically to pregnancy after ART, there have been several reports (including a metaanalysis) that showed a deleterious impact of fibroids upon assisted reproduction, including ICSI. 20,21,23 Thus, while speculative, it is possible that the resolution of the intramural fibroid after treatment with the Sonata System might have played a role in enabling successful ET postablation.…”
Section: Discussionmentioning
confidence: 99%
“…Two factors were significant, namely the size of myomas and the proximity of the uterine cavity [ 12 ]. As reported by Yan et al [ 42 ], a type 3 myoma measuring 2 cm or more situated close to the endometrial lining will have a detrimental effect. As stressed very recently by Freytag et al [ 11 ], although intramural myomas are reported to be associated with poorer pregnancy outcomes than in women without myomas, studies addressing the question of improved conception capacity after myomectomy are few and far between.…”
Section: Non-cavity-distorting Uterine Fibroids and Infertility: Conclusive Remarks From Recent Literature Reports And Meta-analysesmentioning
confidence: 91%